Analysis of early retirement expenses balance from the perspective of age groups - Wan Noor Hayatie Wan Abdul Aziz,; Munira Ismail,; Zaidi Isa,; Wan Nor Munirah Ariffin,; Nurul Husna Jamian, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Many households have trouble managing their finances due to low income, growing living costs and poor saving habits. Effective early retirement planning influences long-term financial stability. Therefore, this study endeavors to examine the pattern of household income influence expenditure across five distinct age cohorts to assess retirement savings adequacy. Specifically investigating whether the income-expenditure differentials at different life stages allow for enough wealth accumulation to support sustainable retirement living standards. A total of 1870 household were chosen in this research focus on Selangor state, the most economically significant state in the country with the highest prevalence of bankruptcy. Selangor state with high population density, varied economic environment, and diversified demographic make it perfect microcosm of Malaysia larger socioeconomic fabric, which improves the findings’ applicability to the country. This study used non-parametric methods to ensure robust statistical analysis due to the non-normal distribution of data, as identified by the Shapiro-Wilk test and confirmed by the ineffectiveness of transformations. Since income, expenses, and balance were not normal across age groups, even though the sample size was big, non-parametric tests had to be used to make sure the analysis was precise and trustworthy. The results show that household income has a significant impact on balance and spending. This study contributes insightful information to the field of retirement and personal finance studies in providing a foundation for future investigations.